Esophagus-Like Bronchus: A Noncommunicating Bronchopulmonary Foregut Malformation. (December 2021) - Weon, Jenny L.; Megison, Stephen; Timmons, Charles F.; Rakheja, Dinesh
We describe a previously unreported bronchopulmonary foregut malformation wherein a segment of a bronchus of the lower lobe of the left lung in a 4-year-old girl was entirely esophageal in structure. No communication was identified between the tracheobronchial tree and the esophagus by radiologic examination or at surgery. The esophagus-like bronchus was associated with an adjacent atretic bronchus and a downstream cavity in the lower lobe of the left lung. The child sought clinical attention because of recurrent pulmonary infections localized to the lower lobe of the lung. We posit that this esophagus-like bronchus is a novel noncommunicating bronchopulmonary foregut malformation.